Silvopastoral systems and global warming: a gas emission balance - Montenegro, Johnny (2002)
A gas emission balance was carried out in SPS located in the Montano Low Forest (MLF), Wet Premontain Forest (WPF), and Tropical Wet Forest (TWF) of Costa Rica. The methane emission from cattle, N2O and CO2 emission from soil, temperature, humidity, carbon, ammonium and nitrate contents, and soil compaction were determined in SPS as well as in natural forest ecosystems. In the SPS located at the MLF and TWF emissions were higher than in natural ecosystems. In both, the N-NH4 soil concentration positively influenced the nitrous oxide gas emission. In the WPF ecosystem, the net emission showed a favorable N2O balance (-1.58 kg of N ha-1 year-1) for the SPS but the natural forest emitted less C (3.51 kg of C ha-1 year-1). The methane emission factor determined was 654 kg CH4 ha-1 year-1 in the WPF, 183 kg CH4 ha-1 year-1 in the TWF and 360 kg CH4 ha-1 year-1 in the MLF. The emission efficiency expressed as g of CH4 kg-1 of produced milk was MLF: 19, WPF: 22 and TWF: 31. The carbon in the soil was higher in the SPS than in the natural forest ecosystems. The annual amount of C per land unit in the arboreal component was higher in the SPS of the WPF and TWF than in the MLF. The lowest balance value (418 kg of C ha-1 year-1) was estimated for the SPS in the TWF and the highest (3911 kg of C ha-1 year-1) for the SPS in the WPF; an intermediate range was estimated for the SPS located in the MLF (2418 kg of C ha-1 year-1). The total emission of N2O was higher in the bovine production systems than in the natural ecosystem, with the exception of the SPS located in the WPF. The emission of carbon dioxide was always higher in the SPS. The total carbon amount stored in the soil profile was higher in the SPS. The balance indicated that all farms evaluated act as originators of greenhouse gases, methane being the main gas affecting the final balance.